2017
DOI: 10.4103/sni.sni_44_17
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical study of rod stress after pedicle subtraction osteotomy versus anterior column reconstruction: A finite element study

Abstract: Background:In an effort to minimize rod fractures and nonunion in pedicle subtraction osteotomy (PSO) constructs, surgeons have adopted multirod constructs and interbody cages. Anterior column realignment (ACR) with posterior column osteotomies is a minimally invasive alternative to PSO in sagittal balance correction, however, there is a paucity of evidence with respect to rod survival.Methods:Three-dimensional (3D) finite-element-model of a T12-sacrum spine segment was used to compare a 25° PSO at L3 and an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
4
31
1
1
Order By: Relevance
“…Most important, rates of pseudarthrosis and rod failure were lower when four rods were placed. This is especially important for patients requiring higher grade osteotomies, given the substantial biomechanical stress created across osteotomy sites [20, 48]. The authors acknowledge the complex relationship between rod fracture and pseudarthrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Most important, rates of pseudarthrosis and rod failure were lower when four rods were placed. This is especially important for patients requiring higher grade osteotomies, given the substantial biomechanical stress created across osteotomy sites [20, 48]. The authors acknowledge the complex relationship between rod fracture and pseudarthrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes of a basic experiment reported that the combination of satellite rods reduced the stress on rods by 59% [ 20 ]. It was reported that usage of satellite rods in patients with Scheuermann kyphosis resulted in greater correction and maintenance of the correction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Основное преимущество заключается в распределении нагрузок между бóльшим числом стержней, что, соответственно, снижает индивидуальную нагрузку на каждый стержень в отдельности. Так, результаты биомеханических исследований, основанных на анализе конечных элементов на кадаверных моделях позвоночника, показали, что при проведении PSO четырехстержневая фиксация обеспечивает снижение нагрузки на основные стержни на 50% при сгибании, на 43% -при боковых наклонах и на 27% -при ротации по сравнению с двухстержневой фиксацией [42]. Результаты другого биомеханического исследования, проведенного J.A.…”
Section: Discussionunclassified